Direct One-Pot Synthesis of Tetrazole Derivatives from Aldehydes under Metal-Free Conditions - Singh, Rajeev; Ahmed, Naseem (Synlett, 2024)
A simple and efficient one-pot protocol has been developed for the synthesis of 1H-tetrazole and 1-methyltetrazole derivatives from aldehydes under mild and metal-free conditions using ammonium azide or methyl azide, respectively. A number of tetrazole derivatives were obtained in moderate to high yields (75–92%) in green solvents at a moderate temperature. These reactions presumably proceed through the formation of a nitrile in situ. The mild conditions and the easy workup and purification make this method highly valuable.
Keywords: tetrazoles; methyltetrazoles; one-pot synthesis; green chemistry